Neuroblastoma of the Urinary Bladder in an Infant - Ahmed Mohamed; Quentin Campbell-Hewson; Hany O. S. Gabra (Georg Thieme Verlag KG, 2019)
As it originates from neural crest cells, Neuroblastoma (NBL) can arise anywhere along the sympathetic chain. However, its occurrence in the urinary bladder (UB) is extremely rare. We present a case of an incidentally diagnosed pelvic NBL arising from the dome of the UB in a 7-month-old infant. The mass was treated with surgical excision only after being classified as a very low risk group according to the International Neuroblastoma Risk Group staging system. The patient was disease free after 5 years of follow-up. Although rare, we suggest that NBL should be considered in the differential diagnosis of UB masses in children and investigated accordingly.